Evaluating the theoretical validity of the PASPOR model for enhancing mathematical communication in teacher education - Jufri Jufri; Asrial Asrial; Asni Johari; Kamid Kamid (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Mathematical communication is a key skill for preservice primary school teachers, enabling them to effectively facilitate understanding in the classroom. Despite its importance, many students in teacher education programs struggle to convey mathematical concepts clearly in both verbal and symbolic forms.Aim: This study aimed to evaluate the theoretical validity of the PASPOR Model—comprising Pairing, Square, Presentation, and Repetition—as an instructional framework designed to enhance mathematical communication in preservice teacher education.Method: A development research approach was applied, based on the Plomp model. Expert validation focused on five core components: syntax, social system, reaction principle, support system, and instructional impact. Data were collected using structured instruments completed by mathematics education experts and analyzed through both quantitative and qualitative techniques.Result: The findings demonstrated high theoretical validity for the PASPOR Model. Expert ratings ranged from 3.68 to 3.97, with reliability coefficients exceeding 0.90 across all components. Experts affirmed the model’s internal consistency, pedagogical relevance, and effectiveness in promoting structured, collaborative mathematical communication among learners.Conclusion: The PASPOR Model is a theoretically sound and pedagogically appropriate instructional model for improving mathematical communication in preservice teacher education. Its structured stages support cooperative learning and reflective interaction. The strong expert agreement endorses its integration into teacher education curricula and provides a foundation for future empirical studies to assess its practical application and adaptability in various learning contexts, including digital platforms.